2021
DOI: 10.47191/jefms/v4-i9-08
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Capital Markets, Inflation, and Demographics on the Growth of Pension Fund Assets in the State Organization of Islamic Cooperation

Abstract: The percentage of pension receipts that is still low is experienced by many developing countries in the continent of Asia and Africa in terms of providing pension funds for their citizens. This study seeks to analyze the effect of growth in pension fund assets in OIC member countries. The measurement of the growth of pension fund assets is viewed through the aspects of the number of stock traded, the equity index, the inflation rate, male labor force participation, female labor force participation, the working… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…In addition, these investments experiences higher unrealized losses and lower return [8]. This finding is in line with [39,40] that pension fund investment may not necessarily increase the standard of living of citizens.…”
Section: Discussion Of Findingssupporting
confidence: 52%
See 1 more Smart Citation
“…In addition, these investments experiences higher unrealized losses and lower return [8]. This finding is in line with [39,40] that pension fund investment may not necessarily increase the standard of living of citizens.…”
Section: Discussion Of Findingssupporting
confidence: 52%
“…Using 13 European countries from period 1999 -2014, and the Panel regression approach; the findings show that the long term characteristics of pension funds have no significant link with European markets efficiency. In another development, Ashari et al, [40] utilized a panel approach from 2010 -2019 in OIC member countries and found slower growth due to existing demographic measures. Specifically, working and retired female participation in pension fund present negative effect on pension investments.…”
Section: The Intermediation Theory By Gurley and Shawmentioning
confidence: 99%